Beburughen Becce’ dalam Saloka Madura Sebagai Nasehat bagi Auditor - Moh. Baqir Ainun; Tyasha Ayu Melynda Sari (Program Study Akuntansi, 2021)
Every ethnicity and culture is unique and contains good ethics for society. Various advice and advice from parents, teachers, and tribal leaders can be conveyed in unique ways such as through the typical proverb of the culture itself. This paper explores how beburghen becce' (good advice) contained in saloka Madura can be advice for auditors in carrying out the audit process so that accounting scandals such as Arthur Andersen and Enron do not recur. The research method used is the study of literature obtained from various sources. This paper explains that beburughen becce' (good advice) contained in saloka Madura such as pakoh ngenneng ka kaju (nails stuck to wood), lakona lakone kennengnganna kennengnge (employees work on the place they live in), mon kerras paakerres (if it is hard it must be crispy), oreng jhujhur mate ngonjhur (honest people die long), and sweet jhe' dhuli kalodhu' pae' jhe' dhuli paloa (sweet, don't swallow bitter, don't immediately spit it out) can provide advice for auditors to carry out audits with independence, responsibility, objectivity, integrity, and skeptical.